A molecular analysis of flower colour development in an ornamental monocot (Anthurium anadraeanum) : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Plant Molecular Biology at Massey University, Palmerston North, New Zealand - Collette, Vern Eddy (Massey University, 2002)
Colour in Anthurium andraeanum spathe and spadix was investigated at the molecular level. A cDNA library was constructed from poly (A)+ RNA isolated from different stages of spathe tissue of the red-flowered anthurium cultivar. Altar. Full-length clones for the flavonoid biosynthetic genes, chalcone synthase, flavanone 3-hydroxylase, dihydroflavonol 4-reductase (DFR) and anthocyanidin synthase were isolated by heterologous screening. The expression pattern of these genes implicates DFR as a prime regulatory target in the spathe, having an independent regulatory mechanism to that of the other three genes. In the spadix, other regulatory targets are suggested. Additional analysis of DFR expression in the spathe revealed a diurnal rhythm to its transcript profile and a model of the possible functional significance of this is presented. Molecular analysis of the genetic model for anthurium spathe colour was performed with three genotypically defined white lines recessive at the O and M loci, revealing a more complex genetic model than that originally proposed. The hypothesis that the O locus encodes a regulatory protein with specific targets is discussed along with various possible identities for M. Several partial Myb cDNA clones were isolated, representing six distinct Myb groups in the anthurium spathe. A full-length cDNA clone for one Myb gene, AaMyb1, was obtained. AaMyb1 encodes a R2R3 Myb protein. It had all the structural features in its DNA binding domain that are conserved in R2R3 Myb proteins as well as an acidic domain in the C-terminus that is a potential activation domain. In sequence comparisons with other Myb proteins, AaMYB1 had high similarity to anthocyanin related Mybs from Zea mays (maize). However, in transient assays, AaMYB1 was unable to restore wild type phenotype in an Antirrhinum majus line, mutated at the anthocyanin Myb locus Rosea1. The expression pattern of AaMYB1, in fact, suggests a role in regulating flavone production in the anthurium spathe. Analyses were done to further investigate the regulation of the anthurium DFR promoter. Specific conserved cis-elements recognised by anthocyanin Myb regulators were found in the promoter fragment. However, transient expression assays showed that the anthurium DFR promoter was activated independently of ROSEA1. The possibility that DFR expression is controlled by several regulatory mechanisms, involving various signal transduction cascades, is discussed.
Keywords: Flamingo lily; Flower genetics; Fields of Research::270000 Biological Sciences::270400 Botany::270402 Plant physiology